Artemether Ameliorates Non-Alcoholic Steatohepatitis by Repressing Lipogenesis, Inflammation, and Fibrosis in Mice - Xu, Jia; He, Xiaoyun; Huang, Xianghui; Zhang, Feng; Ren, Xinxin; Asakiya, Charles; Li, Yue; Huang, Kunlun (Frontiers in Pharmacology, 2022)
Background: Non-alcoholic fatty liver disease (NAFLD) is a widespread disease, but no recognized drug treatment exists. Previous studies have shown that artemether (Art) can ameliorate carbon tetrachloride (CCl4)–induced liver fibrosis in mice. This study sets out to observe the therapeutic impact of Art on non-alcoholic steatohepatitis (NASH). Methods: Model mice were provided with a methionine- and choline-deficient (MCD) diet for 4 weeks or a high-fat diet (HFD) for 28 weeks, respectively, and then treated with Art. RNA sequencing (RNA-Seq) analyzed gene expression changes caused by Art treatment. The molecular mechanism of the therapeutic effects of Art on NASH was studied in the mouse liver and HepG2 cells. Results: Art treatment significantly attenuated hepatic lipid accumulation and liver damage in MCD diet– or HFD-induced NASH mice. The RNA-Seq analysis revealed lipid metabolism as a major pathway suppressed by Art administration, in addition to the regulation of inflammation pathways. Mechanistically, Art reduced lipid accumulation by repressing de novo lipogenesis of sterol regulatory element-binding protein-1c (SREBP-1c), acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-CoA desaturase (SCD1), promoting lipolysis of peroxisome proliferator–activated receptor-γ co-activator-1α (PGC1α), adipose triglyceride lipase (ATGL), and carnitine palmitoyltransferase I (CPT-1a) in NASH mouse liver and HepG2 cells. In addition, Art inhibited the secretion of pro-inflammatory factors and reduced inflammatory infiltration by effectively inhibiting M1 macrophage activation. Furthermore, Art inhibited transforming growth factor-beta 1 (TGF-β), and the SMAD signaling pathway mediates the development of liver fibrosis. Inclusion: Art improved fat deposition by repressing de novo lipogenesis and promoting lipolysis in vivo and in vitro. Furthermore, Art improved inflammation and fibrosis with a significant effect. It is a prospective therapeutic agent for NASH.